Relevance of future snowfall level height in the Peruvian Andes for glacier loss in the 21st century under different emission scenarios - Schauwecker, Simone (2017)
In many regions of Peru, the competition for limited hydrological resources already represents a large risk for conflicts. In this context, and within the circumstances of climate change, there is a great interest in estimating the future loss of Peruvian glaciers. Solid precipitation on glaciers, which affects the shortwave radiation budget via its effects on albedo, in general reduces ablation. For that reason, the height of the upper level of the transition zone between liquid and solid precipitation (snowfall level height) is considered to play a critical role. This snowfall level height is linked to air temperature. The observed and projected warming of the atmosphere is therefore affecting the glaciers amongst others by changing the snowfall level height. Despite the potential significance of these changes for Peruvian glaciers, the relations between snowfall level heights, glacier extents and climate scenarios have been poorly investigated so far. In our study, we first analyse the snowfall level heights over the Peruvian Cordilleras.